“Efecto de tres niveles de compost en el rendimiento del cultivo de repollo (brassica oleraceae L), en yurimaguas” - Ríos Arévalo, Jean Cristian (2014)
This research work entitled "EFFECT OF THREE LEVELS OF COMPOST IN CROP YIELD OF CABBAGE (Brassica oleracea L). IN YURIMAGUAS, The research was carried out between July 2011 and December 2012 in the farm " SAN CARLOS " owned agricultura! technician Toasting Red Edwer located the left side of the road Belaunde Terry, the Loreto region. The aim of determine the effect of three levels of compost on crop yield of cabbage (Brassica oleracea L). In Yurimaguas For the present work experimental design randomized complete block (RCBD) with four treatments and four replications was used. Organic sources TO= No mulch (control), T1 = 5 kg/m2 Compost, Compost T2 = 1 O kg/m2 were applied, T3 = 15 kg/m2 Compost, T3 (15 kg.m -2) obtained the average highest yield, number of leaves per plant, the total plant weight and head weight 27,833.06 kg ha -1 with 10.2 leaves per plant, 997.5 g and 835.0 g respectively head weight statistically outperforming the averages obtained by other treatments. Being also the witness Treatments scored the lowest. averages. The T3 (15 kg.m -2) treatment had the highest average vertical diameter of 17 .3 cm head being statistically equal to the average obtained by the T2 (10 kg. Kg.m -2) who obtained 16.0 cm vertical diameter of the head. The T3 (15 kg. Kg.m -2), T2 (1 O kg. Kg.m -2) and T1 (5kg. Kg.m -2) treatments were statistically equal to each other averages 12.8 cm, 12.0 cm and 11.3 cm in the equatorial diameter of the head respectively statistical average exceeding 9.0 cm TO obtained by the treatment (without composting). The T3 (15 kg.m -2) treatment had the highest B I C to 0.31 and a net profit of SI. 3,256,87 per hectare, followed by T2 (1 O kg.m -2) , TO treatments (no mulch ), who obtained values B I C of 0.3, 0.08 and 0.01 with net profit of S /. 2396.91, S /. 220.31 and SI. 30.29 respectively. Keywords: Treatments, Organic sources, Compost